Robotic-Assisted Total Knee Arthroplasty for Distal Femur Fracture with Lateral Knee Osteoarthritis. (28th April 2021) - Kaneko, Takao; Igarashi, Tadashi; Yoshizawa, Shu; Takada, Kazutaka; Ikegami, Hiroyasu; Musha, Yoshiro
Abstract : Introduction. Open reduction and internal fixation (ORIF) of compound fractures around the knee in elderly patient raise concerns about long-term postoperative external fixation and complications. Total knee arthroplasty (TKA) has been proposed as an alternative solution. We report a case where robotic-assisted (RA) TKA was used to treat lateral knee osteoarthritis (OA) with distal femur fracture. Case Presentation . A 90-year-old female visited our hospital with complications of sustained knee pain after a fall at home. Fracture line from the trochlea to the intercondylar notch was diagnosed on plain radiographs, and prior to this injury, the patient was receiving conservative treatment for lateral OA. We selected a conventional TKA over ORIF because the latter is associated with residual pain and the need for long-term immobilization, which can lead to other complications. However, the fracture site was the entry point for intramedullary rod, and there was concern that the fracture site would be displaced by conventional TKA. Therefore, the unique aspect of the case is that the technique utilized involved robotic milling using the Navio system while temporarily stabilizing the fracture using two tracker pins. RA TKA could determine osteotomy and implant placement by predicting the postoperative patient's soft tissue balance for no medial loosening and lateral contracture. The arthritic cartilage and bone were then methodically removed using the handheld sculptor. After immobilizing the fracture site with a bone grasper before removing the pin tracker, reaming of the femur and insertion of a stem prosthesis with semiconstrained were performed. Primary RA TKA is a viable option for intra-articular fractures in elderly patients with advanced knee osteoarthritis.